Development of E-Module For The Making Of Fried Onion in Basic Culinary Courses in Culinary Studies Education Study Program Indonesian University of Education - Fhera Adelia; Rita Patriasih; Karpin Karpin (Media Pendidikan Gizi dan Kuliner, 2022)
Educators and teaching materials are one of the main components in the learning process. However, in the current pandemic conditions, students are required to study independently through teaching materials as a guide. One of the teaching materials that can support the independent learning process is the electronic module (e-module). Based on information obtained from the lecturer in charge of basic culinary courses, the results of the practice carried out by the Class of 2020 Catering Education students there are still some students whose practice results do not match the criteria of completeness that have been determined. When asked about the material about fried onions through essay questions at the end of the semester there were only 2 people who answered the question well. This study aims to determine whether the e-module for making fried onions is suitable for use in the learning process. Research usingresearch and development methods with the ADDIE model are analysis, design, development, implementation and evaluation. However, researchers limit it only to the development stage. The instruments used in this study were interviews, literature studies and expert validation sheets. The results showed that the e-module for making fried onions according to material, media and language experts was suitable for use. This shows that the e-module for making fried onions developed in this research is suitable for use in teaching basic culinary courses.